PENINGKATAN PEMAHAMAN IMPLEMENTASI PEDOMAN PENYELENGGARA TERTIB ADMINISTRASI (PPTA) PADA ORGANISASI KELUARGA MAHASISWA LEBAK (KUMALA) PERWAKILAN PANDEGLANG SEBAGAI UPAYA MEMAJUKAN ORGANISASI - Bangsawan, Try Adhi; Oktaviani, Via; Afrilian, Alita Harya; Nurfitriani, Widya (Jurnal Abdimas Bina Bangsa, 2024)
Implementing orderly administration is important in running an organization, including student organizations. Lebak Student Family (KUMALA) Pandeglang Representative often experienced difficulties in organizing orderly administration ranging from correspondence, proposals, committee, and the highest form of the organization to the preparation of reports. The methods used in this activity are lectures, discussions, questions and answers, practice, and assignments. As for the results of this service, at the time of the pre-test there were 31.3% of participants had not received information and explanations related to orderly administration. Then after the post-test, 68.8% understood the meaning of orderly administration, 68.8% understood the purpose of implementing orderly administration, and 56.3% understood the impact of orderly administration on the progress of student organizations. This service has an impact on improving the implementation of orderly administration in the Lebak Student Family Organization (KUMALA) Pandeglang Representative